CURRENT STATUS, ANALYSIS AND DEVELOPMENT TRENDS OF TEACHING THE SUBJECT "HISTORY OF UZBEK MUSIC" IN HIGHER MUSIC EDUCATION IN UZBEKISTAN - Nurullayev Farrukh Gaybulloyevich, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This study analyzes the current state of teaching Uzbek Music History within higher music education and outlines key tendencies shaping the field. In contemporary curricula, the subject typically balances national heritage content—maqom traditions, regional performance schools, folk-instrumental practices, and twentieth-century institutional developments—with modern pedagogical expectations for outcomes-based learning. The analysis highlights persistent challenges: uneven integration of archival and field materials, limited assessment alignment with analytical competencies, and a gap between conservatory-style performance training and academically rigorous historiography. At the same time, important positive trends are evident, including strengthened heritage safeguarding agendas, renewed attention to maqom as a national classical canon, and growing use of digital resources for listening analysis and repertoire documentation.